Smoking and the public purse - Christopher Snowdon; Mark Tovey (Institute of Economic Affairs (IEA), 2017)
This discussion paper provides the first estimate of the net effect of smoking on UK taxpayers per annum. Up until now, estimates have used a methodology that typically includes intangible costs, including costs to smokers themselves, while ignoring tangible savings to the state and tax revenues from tobacco duty. This paper estimates a net saving of 14.7 billon per annum at current rates of consumption, with the costs smokers incur significantly outweighed by the sum of tobacco duty paid and old-age expenditures avoided due to premature mortality. The government spends 3.6 billion treating smoking-attributable diseases on the NHS and up to 1 billion collecting cigarette butts and extinguishing smoking-related house fires. But these costs are covered more than four times over by early death savings and tobacco duty revenue. Previous cost-of-smoking studies for the UK have universally ignored savings from premature mortality, meaning their results showed an incomplete picture of the situation faced by taxpayers. Ours is the only study that shows the impact on government finances of a counterfactual scenario in which there is no smoking. This paper is the final instalment of a three-part series looking at three lifestyle factors that are said to be a drain on taxpayers. The first two papers looked at alcohol and obesity respectively. The former incurs a gross cost which is amply offset by alcohol duty revenues. The latter incurs an annual net cost of up to 2.5 billion. The current paper finds that smoking results in a net saving of 19.8 billion. Taken together, Britain's public finances would be 22.8 billion worse off if there were no drinking, smoking or obesity.
Keywords: I18; I13; D03; D04; L51; I18; I13; D03; D04; L51; 330